Divided disasters: examining the impacts of the conflict–disaster nexus for distanced crises in the Philippines. (6th August 2018) - Field, Jessica
Abstract : 'Divided disasters' are conflicts and natural hazard‐induced disasters that occur simultaneously, but in different locations within the same national boundaries. They will place pressure on the same national governance structures, will draw on the same international and national humanitarian resources, and therefore can mutually reinforce the challenges and risks faced by affected populations. Yet, as this paper argues, the impacts do not originate in the direct interaction of these two variables. Rather, they derive, in part, from the management of humanitarian responses to them—namely, through the reprioritisation of attention and the redeployment of resources as driven by the imperatives of 'the good project'. Using a case study of the Philippines, and the parallel emergencies of Typhoon Haiyan (one of the strongest tropical cyclones on record) and the spike in violence in Mindanao in 2013, this paper explores the organisational motivators of humanitarian responses to divided disasters, and assesses their implications for affected populations.